Educação e neoliberalismo: uma análise documental sobre a “Escola da Escolha” em Minas Gerais - Santos, Natalia Oliveira (2024)
This dissertation aims to analyze the full-time high school model of state schools in Minas Gerais, known as the School of Choice, which was developed by the Institute for Co-responsibility for Education (ICE) for the State Department of Education. Constructed based on the high school reform (Law nº 13.415/2017) and the 2018 BNCC (National Common Curriculum Base), this teaching model highlights and exemplifies some aspects of the complex relationships between capital and education. Assuming that the School of Choice is based on neoliberal premises for education, the focus of the research is to understand the historical and social context in which it is embedded, investigating how the neoliberal political-pedagogical project is being proposed in the documents to be implemented in the full-time high school model in the state of Minas Gerais, what interests and motivations determined the construction of the School of Choice, as well as its two structuring concepts: the life project and youth protagonism. To analyze the content of the proposals in the documents for high school in Minas Gerais, the study will use the theoretical framework of Historical-Critical Pedagogy that underpins the social function of high school education. Using these assumptions as an analytical tool, the study aims to verify the impacts and influences of the reform on the formation of young people and the construction of the school curriculum. The research methodology is based on a documentary study and bibliographic research. The main documents to be analyzed will be Law nº 13.415/2017, the final 2018 version of the BNCC (National Common Curriculum Base), Law nº 13.005/2014 which establishes the PNE (National Education Plan) 2014-2024, State Decree nº 47.227/2017, which establishes the implementation of full-time education in the state education network of MG, as well as the analysis of the Training Notebooks of the School of Choice (2019) and some regulations, guidelines, and training manuals for education professionals working in the School of Choice model. The theoretical framework is based on authors from Historical-Critical Pedagogy and thinkers who have historically contextualized the emergence and definition of the concept of neoliberalism.